VIA PT800/P4X533 Series Motherboard : Chipset series support cd rev.64.02 - VIA PT800… (ASUStek Computer Inc., 2003)
Besar file 252 MB, berisi file: Bin, Drivers (AMD, audio, lan, USB2, VIA, VIARAID), Manual, Software (acrobat, afudos, asusupdt, directX, logo, pccillin, probe, screensaver).